Simmel, our Contemporary - Lago, Alessandro (Simmel Studies, 2022)
The cipher of Simmel’s actuality is expressed by the concepts of “tragedy of culture” and “crisis,” which still assume profound explanatory value in his opinion. By crisis the author means the end of the absolute claims of metaphysics – according to an interpretation that was already Wilhelm Dilthey’s – that is, the discovery of thought’s inability to embrace the totality of life and the consequent yielding of the field of philosophy in the face of the development of the natural and human sciences. Simmel is one of the first significant examples of overcoming the traditional language of philosophy and metaphysics thanks to the centrality that “metaphor” assumes in his thought, of which the Philosophy of Money is an excellent example. In fact, monetary relations are taken up here as a metaphor for the whole of modern culture, and this allows Simmel across disciplinary boundaries to discuss decisive aspects of modernity, such as the autonomization of scientific knowledge, changing lifestyles, etc. From this point of view Simmel becomes central to rediscussing the status of the sociological discipline as such. It is not a matter of comparing Simmel with the other classics of sociological theory – making him wear the too narrow shoes of the sociologist – but rather of reading his philosophical and aesthetic contributions also from a sociological perspective. This perspective appears to be not only the hermeneutically most respectful but the one that helps to broaden the often too narrow terrain of social theory.